VD_FINDINFO AP / 2009 / 230 vom 19. November 2007 - VD Tribunal cantonal (2007)
BAIL À LOYER, LOYER, AUGMENTATIONEN GÉNÉRAL, ECCLÉSIASTIQUE, ORGANISATION DE DROIT PUBLIC DES ÉGLISES, DROIT PRIVÉ, CURECONSTRUCTION | 63 al. 1 CO, 67 al. 1 CO, 444 al. 1 ch. 3 CPC, 451 ch. 2 CPC, 451b CPC, 452 al. 1ter CPC, 452 al. 2 CPC, 466 CPC, 471 al. 3 CPC, 13 LTB